Efecto de los acabados en la durabilidad de la madera de 10 especies provenientes de plantación forestal de rápido crecimiento - Salas-Garita, Cynthia; Vargas-Fonseca, Lupita; Moya-Roque, Roger (Instituto Tecnológico de Costa Rica. Vicerrectoría de Investigación y Extensión (VIE). Escuela de Ingeniería Forestal, 2013)
This study evaluated wood color change (ΔE*) and the surface quality in ten tropical wood protected with three finishes (based in wax and polyurethane) and coatings development for tropical conditions in natural (NW) and accelerated (AW) weathering condition. The results showed that the application of these finishes, decreased lightness (L*), increased the redness (a*) and yellowness (b*) parameters in all species. ΔE* values found in different finishes and coatings are cataloged as total change of color. It was found that NW produced the higher ΔE* and defects in the coating than AW. Other important results was that tropical clear wood with natural coating produces the higher ΔE* than dark wood color. L* and b* parameters were the most significantly effects on ΔE* of coatings, but any treatments of surface of wood L*, a* and b* affects ΔE*. The stains and fungal development was observed in polyurethane finishes in NW, but not AW. The irregular and mosaic flaw were not observed. The quality index created, which includes long and short line and switch flaw was lowest in NW and was lowest in waxy finish and the highest polyurethane finish.
Informe final de proyecto de investigación. Código del proyecto: 5402-1401-1014
Keywords: Color; Wood; Madera; Tropical species; Ecosistemas tropicales; Cambio; Color change; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production